PRAKTIK TANGGUNG JAWAB SOSIAL PERUSAHAAN PT. BAKRIE SUMATRA PLANTATIONS(TBK.) UNIT JAMBI - Suwandi, Suwandi (Sekolah Pascasarjana UGM, 2013)
Companies all over the world have implemented corporate social responsibility. This research is aimed toanalyze factors affecting CSR practice by Bakrie SumatraPlantations Unit Jambi, a palm oil plantation company. The CSR practice was hypothesized to be inôuenced by government regulation and corporate strategy. The primary data was collected through survey, interviews, focused group discussion, anddirect observation in the ôeld. Meanwhile, the secondary data was gathered from various documents. The data was analyzed by using quantitative and qualitative approaches.The result shows that thegovernment regulation CSR has no impact on the CSR practice. On the reverse, the corporate commitment and strategy were the decisive factors in the successful of CSR practice. This research also found that the CSR practice has contributedto the improvement of peopleâs economic and social conditions. The prominent weakness is that the CSR policies and strategies were top-down and the participation of local people were limited. The other empirical ônding is that the nucleus-plasma partnership was able to implement the basic principles of CSR which were prevailing generally in different sector of businesses.